Malcolm is downloading a file that is 50.4 Mb. his internet connection has a download speed of 1.2 mb per second. Let t represent the amount of time in seconds it will take to download the file.Write and solve a multiplication equation to find the time in seconds it will take Malcolm to download the file

Answers

Answer 1
Answer: the equation is 1.2t=50.2 And the solution is 42
Answer 2
Answer:

Answer:

42 seconds

Step-by-step explanation:

The equation is 1.2t = 50.4

how to solve:

1.2t = 50.4

first, divide from both sides

1.2t/1.2 = 50.4/1.2

the 1.2t/1.2 cancels out.

so we have 50.4/1.2 left

when you do the math you get the answer 42!

so 42 seconds.


Related Questions

Dave wants to install carpet in his room. The room is rectangular in shape with a length of 16 feet and a width of 12 feet. If the total cost of installing the carpet is $288, what is the unit price of carpet per square foot?
Destiny works on commission as an office supply saleswoman. She sold a computer that cost $700 and received a $126 commission. What percent of her sale is Destiny's commission?
Eli ran for two weeks. During the first week , eli ran 12 miles . During the next week, he ran 15 miles. What is the ratio of the number of miles eil ran the first week to the total number of miles he ran in both weeks?
Samir is an expert marksman. When he takes aim at a particular target on the shooting range, there is a 0.950.950, point, 95 probability that he will hit it. One day, Samir decides to attempt to hit 101010 such targets in a row.
I would like to know if 200 cm is greater or less than 3 m

Lines a and b in the figure above are parallel. What is the value of p? Select one:
A. 12
B. 14
C. 20
D. 24

(Please help!)

Answers

It will be c- 20:
4q and 2(q+30) have to equal the same therefore q=30 which makes both these equations equal.
3p + 4q then have to equal 180 as they are on a straight line so you know q=30 so 4x30=120 so 180-120=60
Then 60/3=20 and that is your answer.
Hope this helps :)

Plz tell me how to solve it by doing the work

Answers

how many does each block represent? need to know in order to solve

noreen made 8 2/3 cups of snack mix for a party. her guest ate 3/4 of the mix. how much snack mix did her guest eat?

Answers

Answer:

6(1)/(2)\text{ cups}

Step-by-step explanation:

Given,

Total snake mix for the party = 8(2)/(3) cups = (26)/(3) cups,

Also, the part of total mix eaten by the guest = (3)/(4)

Thus, the total mix eaten by them = part of mix eaten by them × total mix

= (3)/(4)* (26)/(3)

=(26)/(4)

=6(2)/(4)

=6(1)/(2)\text{ cups}

noreen made 8 and 2/3 cups which after solving becomes 8.666
now the guest ate 3/4 which means 3/4 of 8.66 which is 6.50 which means the guest ate 6 1/2 cups

What total length of ribbon is needed to Line the two long sides of the hat?

Answers

Answer:

Total length of ribbon to line the long sides will be 22 in

Step-by-step explanation:

In the given figure of kite if we draw a line "h" vertically will form two right angle triangles.

Then by applying Pythagoras theorem in both the triangles.

h²= (3x + 5)² + (2x + 1)² ------(1)

h²= (5x + 1)² + 5² ------(2)

By equating both the equations

(3x + 5)² + (2x + 1)² = (5x + 1)² + 25

9x² + 25 + 30x + 4x² + 4x + 1 = 25x² + 10x + 1 + 25

13x² + 34x + 26 = 25x² + 10x + 26

13x² - 25x² + 34x - 10x + 26 - 26 = 0

- 12x² + 24x = 0

12x² - 24x = 0

x² - 2x = 0

x(x - 2) = 0

x = 2

Now we will put x = 2 in the measure of sides of the kite.

Side 1 = (3x + 5)

          = 3×2 + 5

          = 11

Side 2 = (5x + 1)

          = 5×2 + 1

          = 11

Side 3 = (2x + 1)

          = 2×2 + 1

          = 5

Therefore, Total length of ribbon to line the long sides will be = 11 + 11

= 22 in.

Your answer will be D-22.

Please help me with this math paper????

Answers

so you find the ones that are divided by the number of boxes as shown below
The first image is 1/6 of 1/2  The second image is 2/3 of 1/4  The third image is 4/5 of 7/8 and the last image is 1/6 of 1/2

F(x)=2x^2+7x-5+g(x)=-8x^2-3x+5

what is g(x) + f(x)

Answers

f(x) = 2x² + 7x - 5
g(x) = -8x² - 3x + 5

g(x) + f(x)
-8x² - 3x + 5 + 2x² + 7x - 5
-8x² + 2x² - 3x + 7x + 5 - 5
-6x² + 4x + 0

-2x(3x - 2)